Desenvolvimento e avaliação inicial de um jogo educativo para avaliação de comportamentos pré-aritméticos - Gris, Gabriele (Universidade Federal de São Carlos, 2021)
Some difficulties faced by Brazilian students in Mathematics may reflect insufficient learning from the first years of schooling. Assessment instruments developed systematically and thoroughly can contribute to the mapping of basic repertoires. This work aimed to develop an educational game to assess pre-arithmetic behavior in children at the beginning of school education. Chapter 1 aimed to identify and operationally describe the predictors and indicators of success in arithmetic through a systematic literature review. We reviewed 13 studies - 11 longitudinal and two cross-sectional - and identified 31 predictors and 15 indicators of success. We observed large conceptual and operational dispersion, and it was not possible to identify a consensus on basic skills that are important for later learning in arithmetic. After reviewing developmental studies, we conducted a systematic literature review with an emphasis on behavior-analytic production. Chapter 2 aimed to identify the main characteristics of studies in Behavior Analysis that investigate pre-arithmetic repertoires and discuss the adequacy of the concept of pre-arithmetic skills. Twenty-one studies were included for analysis, divided between studies on numerical conceptual behavior and curriculum proposals that mainly cover relations between numerals and sets. We also discuss the adequacy of the concept of pre-arithmetic skills and propose that the set of studies identified be named "pre-arithmetic behavior". After revising the first two chapters, we operationalized an educational game's tasks to evaluate pre-arithmetic behaviors and collected validity evidence based on the content of Korsan: Pre-Arithmetic (Chapter 3). After grouping and applying inclusion and exclusion criteria, 74 objective-behaviors remained that were translated into game tasks. Semantic, usability, and engagement analysis were conducted with two participants (8 and 10 years old). Content analysis was also performed after consulting three experts. Subsequently, it was evaluated the alignment between proposed in-game tasks and Base Nacional Comum Curricular based on the analysis of four experts. In the experts' evaluation, the game content is considered appropriate for evaluating pre-arithmetic repertoires. We identified the need to change the visual and wording aspects of the instructions to fit the target audience best. In study 4, we collected evidence to refine the instrument by mainly applying the game to a younger target audience. Seven children, aged between 4 and 8 years old, participated in the study. As anticipated by experts in the challenge level analysis, we identified tasks of different difficulty levels, one of the components in the alignment assessment. Adjustments are suggested so that the game works as a suitable assessment tool while also fulfilling good games' engagement and fun goals.
Development and initial assessment of an educational game to assess pre-arithmetic behaviors
Keywords: Pré-aritmética; Jogo educativo; Análise do comportamento; Educação infantil; Ensino Fundamental; Pre-arithmetic; Educational game; Behavior analysis; Child education; Elementary School; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS